Impact of stroke work on the ability of left ventricular mass to account for pressure effects on function in a community with prevalent systemic flow-dependent hypertension. Issue 10 (October 2021) - Bello, Hamza; Woodiwiss, Angela J.; Naran, Ravi; Peterson, Vernice R.; Libhaber, Carlos D.; Mmopi, Keneilwe N.; Mthembu, Nonhlanhla; Masiu, Mohlabani; Da Silva Fernandes, Daniel; Bamaiyi, Adamu J.; Peters, Ferande; Sareli, Pinhas; et al.
Abstract : Aims: To determine whether the confounding influence of stroke work on left ventricular mass (LVM) limits the ability of LVM to detect hypertensive LV dysfunction in systemic flow-dependent hypertension. Methods: In a community with prevalent systemic flow-dependent hypertension ( n  = 709), arterial haemodynamics, LVM and LV function were determined using central arterial pressure, aortic velocity and diameter measurements in the outflow tract, and echocardiography with tissue Doppler imaging. Results: In multivariate models, stroke work showed markedly stronger relations with LVM index (LVMI) than blood pressure load [central arterial SBP (SBPc), backward wave pressure (Pb), 24-h SBP] ( P  < 0.0001 for comparisons). In contrast, although SBPc, Pb, and 24-h SBP were inversely associated with myocardial tissue shortening ( s' ) and lengthening ( e' ) velocity, stroke work was not. With adjustments for stroke work, positive relationships between SBPc, Pb, or 24-h SBP and LVMI were eliminated ( P  = 0.20 to P  = 0.89), but strong relations between BP and s', e' or E / e' ( P  = 0.009 to P  < 0.0001) remained. In mediation analysis, stroke work fully accounted for BP effects on LVMI, but explained none of the effects of BP on LV function. Hence LVMI accounted for little of the impact of BP load on LV function. Although LVMI beyond stroke work (inappropriate LVM) improved on relations between LVMI and s', it failed to improve on relations with e' or E / e' and contributed little beyond LVMI to the impact of BP on LV function. Conclusion: In systemic flow-dependent hypertension, the impact of stroke work markedly limits the ability of LVM to account for adverse effects of hypertension on LV function. Abstract : Supplemental Digital Content is available in the text